Attitudes towards family formation among men attending fertility counselling. (August 2018) - Sylvest, R.; Koert, E.; Birch Petersen, K.; Malling, G.M.H.; Hald, F.; Nyboe Andersen, A.; Schmidt, L.
Abstract: Men and women are increasingly postponing childbearing until an age where fertility has decreased, meaning that they might have difficulties in achieving their desired family size. This study explored childless men's attitudes towards family formation. Data were collected through semi-structured qualitative interviews with 21 men attending the Fertility Assessment and Counselling Clinic in Copenhagen or Horsens, Denmark. Data were analysed using content analysis. The men envisioned a nuclear family with their own biological children, but they experienced doubts and ambivalence about parenthood and feeling 'ready'. Their lack of readiness was linked to their awareness of the sacrifices and costs involved with parenthood, and their belief that they could safely delay parenthood. The men did not consider that they may be unable to have their own biological children. This study highlights the importance of considering men's attitudes and preferences towards family formation when understanding couples' decision-making. Contrary to common understanding, the findings show that men are as concerned with the planning and timing of parenthood as women, but their knowledge of the age-related decline in fertility is poor. Men need to gain more awareness of the limitations of fertility and the impact of female and male age on the ability to achieve parenthood aspirations.